Parents’ attitudes towards their children’s practice of sports activity - ماضي انجيلا (Latakia University Journal -Medical Sciences Series, 2023)
This research aims to identify the attitudes of parents towards their children’s practice of sports activity and to ask about the differences between their attitudes according to the gender variable. A standardized questionnaire was distributed on internet to measure parents’ attitudes towards their children’s sports activity designed by Dodo (2011) to a sample of 99 parents. The results showed that parents adopt positive attitudes towards their children’s exercise of sports activity, which proved the validity of our first hypothesis, as it was found that there are those differences with regard to their positive attitudes towards their children’s practice of sports activities and for the benefit of parents.